Distributional effects of preferential and multilateral trade liberalization: the case of Paraguay - Elizabeth Jane Casabianca (FIW - Research Centre International Economics, 2012)
In this paper I apply Porto (2006) to Paraguay using household level data. The aim is to assess the distributional impact of the preferential and multilateral trade liberalization in a small member country. I also follow Nicita (2009) assuming incomplete pass-through on prices of traded goods which in turn influence both household consumption and earnings of household members in the labour market. I estimate these effects highlighting the difference between the impact of the preferential trade agreement and the multilateral one. Finally, I am able to depict if and who trade integration has benefited.
Keywords: D1; F1; J3; R2; 330; Household welfare; Paraguay; Pass-through; Trade and Poverty